Risk Factors Associated with the Prevalence of Obesity among University Teachers - Dr. Mohibullah Khan Marwat,; Muhammad Safdar Ali,; Yasir Ali,; Nadeem Ahmad,; Rana Rizwan Ul Haq,; Samera Saman,; Kashif Mehmood, (Al-Qanṭara, 2023)
Background: Obesity is now a global epidemic. There is strong link between physical inactivity and obesity. Similarly, unhealthy eating habits are also associated with obesity. The menace of overweight and obesity has been moving on fast pace in educated communities including university teachers. Objectives: The present study was conducted with the following three different objectives: to find out risk factors associated with the obesity among university teachers; to determine the age at onset of the obesity among university teachers; and to determine the prevalence of obesity among the university teachers. Methodology: It was an epidemiological study, which evaluated the risk factor and prevalence of the obesity in university teachers. The study was conducted using a cross-sectional research design, in which university teachers of different universities of District Abbott Abad participated. The questionnaire used in this study consisted of 5 demographic questions and other questions were divided into two parts to measure food habits and sedentary lifestyle. Results: A total number of 385 university teachers, with an average age of 38.25 participated in the study. Of the 385 participants, only 27.5% reported taking part in a moderate level of physical activity and only 16.9% participated in the physical activities on daily basis. However, 72.5% of university teachers who participated in this study were living a sedentary lifestyle and 84.7% of university teachers reported having unhealthy eating habits. In the present study, the prevalence of overweight and obesity was 26.5% and 64.2% respectively. Statistically significant difference (p =0.000, < 0.05) between prevalence of obesity among university teachers was found. Key words: Lifestyle, Diet, Risk Factor, University, Teachers, Overweight, Obesity